Knowledge, attitudes and use of anabolic-androgenic steroids among male gym users: A community based survey in Riyadh, Saudi Arabia - Fares F Alharbi; Islam Gamaleddin; Samar F Alharbi; Omar Almodayfer; Fahad Allohidan; Mohammed Alghobain; Asaad Arafah; Khaled Al-Surimi (Elsevier, 2019)
Recreational use of anabolic-androgenic steroids (AAS) is a growing worldwide public health concern. However, studies assessing the level of awareness and knowledge of its effects on health are fairly limited, especially in developing countries, including Saudi Arabia. This community-based cross-sectional study was conducted to assess knowledge, attitudes and practices among male gym members toward AAS in Riyadh (Saudi Arabia) from March to October 2016. Twenty gyms were randomly selected from four different geographical regions (clusters) within Riyadh. In total, 482 participants responded to the self-administered anonymous questionnaire, which covered socio-demographic data, data assessing knowledge, attitude and behavior related to AAS use. The mean (±standard deviation) age of study participants was 27.2 (±6.9) years. Among these, 29.3% of participants reported having used AAS, while the majority (53.5%) reported hearing of AAS use, mostly through friends. Most study participants reported awareness of the effects of AAS on muscle mass, body weight and muscles strength (53.2%, 51.1% and 45.5%, respectively). In contrast, a higher proportion of study participants were unaware of the side-effects of AAS use. A high proportion of study participants (43.2%) reported that they had been offered AAS and 68.7% believed that AAS are easily accessible. Most of the gym users (90.1%) reported never having used any narcotics or psychoactive drugs. Regression analysis revealed that use of anabolic-androgenic steroids is significantly associated with "weight lifting practice" OR [95%CI] = 1.9[1.02 − 3.61], P = 0.044; "using supplementary vitamins, OR [95%CI] = 7.8[4.05 − 15.03], P < 0.0001, knowing anyone using anabolic-androgenic steroids' OR [95%CI] = 7.5[3.78 − 14.10], P < 0.0001, and someone advised Gym users to take anabolic-androgenic steroids" OR [95%CI] = 2.26[1.23 − 4.14], P < 0.008. Our findings suggest that the level of awareness regarding the possible side-effects of AAS is fairly limited. Thus, efforts directed toward educating the public and limiting access to AAS as well as health policy reforms are crucial to reduce future negative implications of AAS use. Keywords: Androgenic anabolic steroids, Steroids, Drug abuse, Steroid abuse, Gym users, Addiction, Substance abuse, Saudi Arabia